Jacket made of nanometer self-cleaning fabric and preparation process of jacket
By combining carbon nanotube/TiO2 composite nanomaterial with the substrate fabric and performing thermal setting stretching, the problem of low self-cleaning efficiency of the jacket under low light conditions is solved, and stronger photocatalytic self-cleaning ability and conductivity are achieved.
Patent Information
- Application Number
- CN202411948620.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-25
AI Technical Summary
The existing windbreaker made of photocatalytic self-cleaning fabrics has low self-cleaning efficiency under low light conditions, and the photocatalyst is not fast enough to bind to the fiber, which is easy to fall off, affecting the feel and uniform dispersion.
Carbon nanotube/TiO2 composite nanomaterial and substrate fabric are used for impregnation treatment, and heat-setting tensile treatment is carried out to improve the dispersion and fastness of the photocatalyst and enhance the photocatalytic efficiency.
The photocatalytic self-cleaning ability of the jacket under low light conditions is improved, the electrical conductivity and stain resistance of the fabric are enhanced, and the problem of low self-cleaning efficiency in the prior art is solved.
Smart Images

Figure CN119867408A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabric preparation, and in particular to a jacket made of nano self-cleaning fabric and a preparation process thereof. Background Art
[0002] Woven fabrics are made of interlaced yarns, and are woven on a loom by weft and warp yarns in a certain pattern. They are also called shuttle fabrics. Woven fabrics can use a variety of different yarns and weaving techniques to produce a variety of textures, patterns and thicknesses. Jackets are a widely used type of woven fabric.
[0003] As a must-have equipment for outdoor sports, the waterproof and anti-fouling properties of jackets are crucial. However, during the use of jackets, pollutants such as sewage and mud are easily attached, which will affect the breathability of the jackets. Therefore, jackets need to have a certain self-cleaning ability. In the photocatalytic self-cleaning surface technology, there are also some problems such as the inorganic TiO2 particles are not firmly bonded to the fiber, easy to fall off, affecting the fiber feel, and difficult to disperse evenly on the fiber surface. At the same time, the condition of photocatalytic self-cleaning is that it can only be eliminated under continuous sunlight. When it is located in non-sunlight and low-light conditions, the photocatalytic effect will be weakened and it is not suitable for non-outdoor textile functional treatment.
[0004] Therefore, it is necessary to improve the preparation method of the jacket made of nano self-cleaning fabric in the prior art to solve the above problems. Summary of the invention
[0005] The present invention overcomes the deficiencies of the prior art and provides a jacket made of nano self-cleaning fabric and a preparation process thereof, aiming to solve the defect that the jacket made of photocatalytic self-cleaning fabric in the prior art has low self-cleaning efficiency under low light.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a preparation process of a jacket made of nano self-cleaning fabric, comprising the following steps:
[0007] S1: immersing the base fabric in an alkaline solution for 1-2 hours, taking it out and drying it, and then performing a surface active treatment to obtain a pretreated base fabric;
[0008] S2: adding carbon nanotube / TiO2 composite nanomaterial into water to obtain carbon nanotube / TiO2 composite nanomaterial solution, immersing the pretreated base fabric in S1 into the carbon nanotube / TiO2 composite nanomaterial solution for 2-4 hours, taking out and drying to obtain a treated fabric;
[0009] S3: subjecting the once treated fabric in S2 to a heat setting and stretching treatment for 10-20 minutes to obtain a nano self-cleaning fabric;
[0010] S4: Sewing the nano self-cleaning fabric described in S3 to the outer layer of the jacket to obtain a jacket made of the nano self-cleaning fabric.
[0011] In a preferred embodiment of the present invention, the base fabric is a polyester / silver composite fabric, the warp yarn density is 25-30 yarns / cm, and the weft yarn density is 45-50 yarns / cm.
[0012] In a preferred embodiment of the present invention, the warp yarn of the base fabric is a polyester / silver composite yarn, and the weft yarn is a polyester yarn. The warp yarn production process is to use the polyester fiber as the core yarn and the silver nanowire as the wrapping yarn for wrapping spinning. The number of polyester fibers and silver nanowires in each warp yarn is 2-3F and 4-5F respectively, and the diameter of the silver nanowire is 200-300nm. The fineness and number of polyester fibers in the warp yarn and the weft yarn are consistent, and the fineness is 3-5D respectively.
[0013] In a preferred embodiment of the present invention, the alkaline solution in S1 is a sodium hydroxide solution with a concentration of 10-15%, and the surface active treatment is to spray a 0.5-1% methyl methacrylate silane solution on the base fabric after being immersed in the alkaline solution, and the spraying time is 30-45 minutes.
[0014] In a preferred embodiment of the present invention, the preparation method of the carbon nanotube / TiO2 composite nanomaterial in S2 is as follows:
[0015] S21: adding polyacrylonitrile and TiO2 powder into dimethyl sulfoxide to obtain a polyacrylonitrile TiO2 solution;
[0016] S22: placing carbon nanotubes into the polyacrylonitrile TiO2 solution in S21, and obtaining a carbon nanotube / TiO2 precursor sol by ultrasonic dispersion;
[0017] S23: drying and grinding the carbon nanotube / TiO2 precursor sol in S22, and then calcining to obtain a preliminary carbon nanotube / TiO2 composite nanomaterial;
[0018] S24: irradiating the carbon nanotube / TiO2 composite nanomaterial in S23 with ultraviolet light at a wavelength of 340-380 nm to obtain a carbon nanotube / TiO2 composite nanomaterial.
[0019] In a preferred embodiment of the present invention, the mass ratio of polyacrylonitrile, TiO2, dimethyl sulfoxide and carbon nanotubes in the carbon nanotube / TiO2 precursor sol in S22 is 10-20:30-40:40-50:20-30.
[0020] In a preferred embodiment of the present invention, the particle diameter of the carbon nanotube / TiO2 composite nanomaterial in S2 is 100-300 nm, and the solution concentration of the carbon nanotube / TiO2 composite nanomaterial is 10-12%.
[0021] In a preferred embodiment of the present invention, electric field treatment is performed during the impregnation process of the pretreated base fabric in S2, the electric field treatment field strength is 0.33-2.94 kV / m, the electric field is a uniform electric field, and the direction of the electric field is parallel to the warp direction of the base fabric.
[0022] In a preferred embodiment of the present invention, the temperature of the heat setting treatment in S3 is 110-130° C., the stretching amplitude during the heat setting treatment is 1.5-2, and the stretching direction is parallel to the warp direction of the base fabric.
[0023] In order to achieve the above-mentioned purpose, the second technical solution adopted by the present invention is: a jacket made of nano self-cleaning fabric.
[0024] The present invention solves the defects existing in the background technology and has the following beneficial effects:
[0025] (1) The present invention provides a preparation process for a jacket made of nano self-cleaning fabric, wherein the base fabric is immersed in a carbon nanotube / TiO2 composite nanomaterial solution and the fabric is stretched during the heat setting process, so that the photogenerated electrons generated by titanium dioxide can be quickly transferred to the carbon nanotubes, thereby avoiding the recombination of electrons and holes. The fabric fibers after heat setting are arranged more tightly and orderly. Compared with the jacket made of nano self-cleaning fabric in the prior art, the improved photocatalytic efficiency and increased active sites can make the self-cleaning ability stronger, which is conducive to multiple reflections and scattering of light between fibers and can broaden the absorption range of self-cleaning light, thereby solving the defect of low self-cleaning efficiency of jackets made of photocatalytic self-cleaning fabrics in the prior art under low light conditions.
[0026] (2) In the present invention, silver nanowires can absorb and scatter visible light and ultraviolet light due to their surface plasmon resonance effect. Compared with the prior art, they help to improve the photocatalytic efficiency under low light conditions and form a continuous conductive path, which helps to improve the conductivity of the fabric, thereby enhancing the electron transfer efficiency in the photocatalytic reaction and improving the photocatalytic self-cleaning ability under low light conditions.
[0027] (3) In the present invention, heat setting and stretching can improve the tightness of the fabric. The improvement of the tightness of the fabric makes the fibers or yarns arranged more tightly and orderly. This tight arrangement can form a tiny protrusion structure on the surface of the fabric through a special process. Compared with the prior art, the micro-protrusions also affect the diffusion and mass transfer process of the reactants on the surface of the fabric, promote the effective contact and reaction between the reactants and the photocatalyst, and improve the photocatalytic self-cleaning reaction under low light conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 It is a method step diagram of a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0032] like Figure 1 As shown, a preparation process of a jacket made of nano self-cleaning fabric comprises the following steps:
[0033] S1: Immerse the base fabric in an alkaline solution for 1-2 hours, take it out and dry it, and then perform surface activity treatment to obtain a pre-treated base fabric; alkaline solution treatment can increase the surface activity of the fabric, which helps the subsequent surfactant to better adhere to the fabric. Surface activity treatment can increase the adhesion between the fabric surface and the photocatalytic material.
[0034] S2: Add carbon nanotube / TiO2 composite nanomaterials into water to obtain carbon nanotube / TiO2 composite nanomaterial solution, immerse the pretreated base fabric in S1 in the carbon nanotube / TiO2 composite nanomaterial solution for 2-4 hours, take out and dry to obtain a treated fabric; by introducing carbon nanotubes into TiO2, the spectral response range of TiO2 can be broadened, and its absorption of visible light can be increased, which helps to improve the photocatalytic performance under non-ultraviolet light conditions. The rich functional groups on the surface of carbon nanotubes enable them to have good adsorption capacity for organic matter, and can adsorb pollutants to the surface of the composite material, further improving the photocatalytic efficiency. The carbon nanotube / TiO2 composite material can produce more active groups, which can effectively improve the photocatalytic performance of TiO2. Carbon nanotubes, as a channel for the transmission of photogenerated carriers, accelerate the charge separation efficiency and enhance the kinetic process of the catalytic reaction. The rich functional groups on the surface of carbon nanotubes enable them to have good adsorption capacity for organic matter, and can adsorb pollutants to the surface of the composite material, further improving the photocatalytic efficiency.
[0035] S3: The once treated fabric in S2 is subjected to heat setting and stretching treatment for 10-20 minutes to obtain a nano self-cleaning fabric; the heat setting and stretching treatment can improve the dispersibility of the nano material in the fabric, making the photocatalyst more evenly distributed on the surface of the fabric, thereby increasing the photocatalytic active sites and improving the photocatalytic efficiency.
[0036] S4: Sewing the nano self-cleaning fabric in S3 to the outer layer of the jacket to obtain a jacket made of the nano self-cleaning fabric.
[0037] A preparation process for a jacket made of nano self-cleaning fabric, wherein a base fabric is immersed in a carbon nanotube / TiO2 composite nanomaterial solution and the fabric is stretched during heat setting, so that photogenerated electrons generated by titanium dioxide can be quickly transferred to the carbon nanotubes, thereby avoiding the recombination of electrons and holes. The fibers of the fabric after heat setting are arranged more closely and orderly, and the improved photocatalytic efficiency and increased active sites can make the self-cleaning ability stronger, which is conducive to multiple reflections and scattering of light between fibers and can widen the absorption light range of self-cleaning, thereby solving the defect of low self-cleaning efficiency of jackets made of photocatalytic self-cleaning fabrics in the prior art under non-sunlight.
[0038] The base fabric is a polyester / silver composite fabric with a warp density of 25-30 strands / cm and a weft density of 45-50 strands / cm. Silver and carbon nanotubes work synergistically to provide a carrier for the photogenerated electrons generated by TiO2 under visible light or ultraviolet light excitation. It has a strong electron transport capacity and can effectively inhibit the recombination of photogenerated electron-hole pairs, thereby improving the photocatalytic efficiency. The warp and weft densities help to form a micro-nano rough surface, which can increase the scattering and absorption of light, thereby improving the photocatalytic efficiency under low light conditions.
[0039] The warp yarn of the base fabric is a polyester / silver composite yarn, and the weft yarn is a polyester yarn. The warp yarn production process is to use polyester fiber as the core yarn and silver nanowire as the wrapping yarn for wrapping spinning. The number of polyester fibers and silver nanowires in each warp yarn is 2-3F and 4-5F respectively, and the diameter size of the silver nanowire is 200-300nm. The fineness and number of polyester fibers in the warp and weft yarns are consistent, and the fineness is 3-5D respectively. Silver nanowires can absorb and scatter visible light and ultraviolet light due to their surface plasma resonance effect, which helps to improve the photocatalytic efficiency under low light conditions. Silver nanowires can form a continuous conductive path, which helps to improve the conductivity of the fabric, thereby enhancing the electron transfer efficiency in the photocatalytic reaction. Silver nanowires can improve the anti-pollution ability of the fabric, reduce the accumulation of pollution under low light conditions, and thus improve the self-cleaning efficiency.
[0040] The alkaline solution in S1 is a sodium hydroxide solution with a concentration of 10-15%, and the surface active treatment is to spray a 0.5-1% methacrylate silane solution on the base fabric after being immersed in the alkaline solution, and the spraying time is 30-45 minutes. The alkaline solution treatment can increase the hydrophilicity of the fabric, help the photocatalytic material to better adhere to the surface of the fabric, and improve the photocatalytic efficiency. The methacrylate silane coating can increase the surface roughness of the fabric, increase the contact angle of water droplets and oil stains on the surface of the fabric, and make it difficult to spread and penetrate, thereby improving the anti-fouling ability.
[0041] The preparation method of the carbon nanotube / TiO2 composite nanomaterial in S2 is as follows:
[0042] S21: adding polyacrylonitrile and TiO2 powder into dimethyl sulfoxide to obtain a polyacrylonitrile TiO2 solution;
[0043] S22: placing carbon nanotubes into the polyacrylonitrile TiO2 solution in S21, and obtaining a carbon nanotube / TiO2 precursor sol by ultrasonic dispersion;
[0044] S23: drying and grinding the carbon nanotube / TiO2 precursor sol in S22, and then calcining to obtain a preliminary carbon nanotube / TiO2 composite nanomaterial;
[0045] S24: irradiating the carbon nanotube / TiO2 composite nanomaterial in S23 with ultraviolet light at a wavelength of 340-380 nm to obtain the carbon nanotube / TiO2 composite nanomaterial.
[0046] After loading carbon nanotubes, the specific surface area of the sample increases, which helps to increase the contact area between the photocatalyst and the pollutants and improve the efficiency of the photocatalytic reaction. Through calcination treatment, the obtained carbon nanotube / TiO2 composite nanomaterial has better chemical stability and crystallization properties, which helps to improve the durability and efficiency of the material in practical applications. Ultraviolet irradiation treatment helps to further activate and stabilize the photocatalytic activity of the carbon nanotube / TiO2 composite material, so that the material can maintain a high self-cleaning efficiency even under low light conditions.
[0047] After polyacrylonitrile and carbon nanotubes are mixed, under the action of surface tension, carbon nanotubes tend to be arranged along the axial orientation of nanofibers, which improves the orientation of carbon nanotubes. Carbon nanotubes with high orientation are more conducive to the rapid transmission of electrons, reduce the probability of electron recombination during the transmission process, and further improve the photocatalytic efficiency. Carbon nanotubes with high orientation can more effectively form a close contact interface with titanium dioxide, which is conducive to the effective separation of photogenerated electrons and holes at the interface. Carbon nanotubes with high orientation can more effectively absorb and transmit light energy, thereby improving the photocatalytic activity of the composite catalyst under visible light. Carbon nanotubes with high orientation can more effectively promote the dispersion of titanium dioxide, form more active sites, and are conducive to the photocatalytic reaction.
[0048] The mass ratio of polyacrylonitrile, TiO2, dimethyl sulfoxide and carbon nanotubes in the carbon nanotube / TiO2 precursor sol in S22 is 10-20:30-40:40-50:20-30. The photocatalytic activity can be significantly affected by adjusting the loading amount of TiO2 on the carbon nanotubes. The appropriate mass ratio can improve the photocatalytic performance of TiO2 and increase its degradation rate, thereby improving the self-cleaning efficiency. The tubular structure and large specific surface area of the carbon nanotubes increase the specific surface area of the composite material after loading, increase the available active centers, thereby increasing the concentration of oxygen and organic matter on the TiO2 surface, which helps to improve the self-cleaning efficiency.
[0049] The particle diameter of the carbon nanotube / TiO2 composite nanomaterial in S2 is 100-300nm, and the solution concentration of the carbon nanotube / TiO2 composite nanomaterial is 10-12%. Carbon nanotubes loaded with TiO2 can enhance the intensity of photocurrent and improve the efficiency and rate of the photocatalytic process of titanium dioxide.
[0050] During the impregnation process of the pre-treated base fabric in S2, an electric field treatment is performed, and the field strength of the electric field treatment is 0.33-2.94 kV / m, the electric field is a uniform electric field, and the direction of the electric field is parallel to the warp direction of the base fabric. Under the combined action of the electric field force and the Coulomb force, polyacrylonitrile and carbon nanotubes are also oriented. In particular, when polyacrylonitrile and carbon nanotubes are prepared into nanofibers together, the combined action of this electric field force and the Coulomb force further promotes the orientation of the carbon nanotubes. The molecular chains of polyacrylonitrile will be arranged in an orderly manner along the axial direction of the electric field, and can induce the carbon nanotubes to be oriented in the same direction. This orientation induction effect is achieved through the interaction force between the polyacrylonitrile molecular chains and the carbon nanotubes, so that the orientation degree of the carbon nanotubes in the electric field is improved.
[0051] Through the action of electric field, the directional arrangement of carbon nanotubes can be achieved. The directional carbon nanotubes can improve the separation efficiency of photogenerated electrons and holes, thereby improving the photocatalytic efficiency. Silver nanowires have a surface plasma resonance effect, which can enhance the visible light absorption of titanium dioxide. When the direction of the electric field is consistent with that of the silver nanowires, the electric field can guide the migration of photogenerated charges and promote the absorption and utilization of titanium dioxide.
[0052] The temperature of the heat setting treatment in S3 is 110-130℃, and the stretching amplitude during the heat setting treatment is 1.5-2. Heat setting stretching can improve the tightness of the fabric. The improvement of the tightness of the fabric makes the fibers or yarns arranged more tightly and orderly. This tight arrangement can form tiny protrusions or grooves on the surface of the fabric through special processes, which can increase the surface roughness of the fabric and increase the contact angle of water droplets and oil stains on the surface of the fabric, making it difficult to spread and penetrate. More microchannels or pore structures can be formed between the tightly arranged fibers or yarns. These structures can increase the number of reflections and scattering of light inside the fabric, thereby increasing the contact opportunities and reaction efficiency of light and photocatalysts.
[0053] In the process of increasing the compactness, the internal stress of the yarn changes and micro-bumps are generated on the surface of the yarn. The micro-bump structure on the surface of the fabric can significantly increase its surface area. A larger surface area means that the titanium dioxide photocatalyst can receive more light, thereby stimulating more photocatalytic reactions. The micro-bumps can also react to sites, making it easier for active oxygen species to contact and react with pollutants. In addition, the micro-bumps also affect the diffusion and mass transfer process of reactants on the surface of the fabric, promoting effective contact and reaction between reactants and photocatalysts.
[0054] To achieve the above object, the second technical solution adopted by the present invention is: a jacket made of nano self-cleaning fabric. The nano self-cleaning fabric in S4 is combined with the outer layer of the jacket by sewing.
[0055] Embodiment 1
[0056] This embodiment provides a jacket made of nano self-cleaning fabric, and the preparation process is as follows:
[0057] S1: The polyester / silver composite fabric is immersed in a 10% sodium hydroxide solution for 2 hours. The warp yarn of the polyester / silver composite fabric is a polyester / silver composite yarn, and the weft yarn is a polyester yarn. The warp yarn production process is to use polyester fiber as the core yarn and silver nanowire as the wrapping yarn for wrapping spinning. The number of polyester fibers and silver nanowires in each warp yarn is 3F and 5F respectively, and the diameter of the silver nanowire is 150nm. The fineness and number of polyester fibers in the warp yarn and weft yarn are consistent, and the fineness is 4D respectively. The warp yarn density is 30 strands / cm, and the weft yarn density is 45 strands / cm. After taking out and drying, a 0.5% methyl methacrylate silane solution is sprayed on the polyester / silver composite fabric for 30 minutes to obtain a pretreated base fabric.
[0058] S2: Add polyacrylonitrile and TiO2 powder into dimethyl sulfoxide to obtain polyacrylonitrile TiO2 solution, put carbon nanotubes into the polyacrylonitrile TiO2 solution, and obtain carbon nanotube / TiO2 precursor sol by ultrasonic dispersion. The mass ratio of polyacrylonitrile, TiO2, dimethyl sulfoxide and carbon nanotubes in the carbon nanotube / TiO2 precursor sol is 10:35:45:20. The carbon nanotube / TiO2 precursor sol is dried, ground, and calcined to obtain preliminary carbon nanotube / TiO2 composite nanomaterial. The carbon nanotube / TiO2 composite nanomaterial in S23 is irradiated with ultraviolet light at a wavelength of 360nm to obtain carbon nanotube / TiO2 composite nanomaterial. Nanotube / TiO2 composite nanomaterial, the particle diameter of carbon nanotube / TiO2 composite nanomaterial is 200nm; adding carbon nanotube / TiO2 composite nanomaterial into water to obtain carbon nanotube / TiO2 composite nanomaterial solution, the solution concentration of carbon nanotube / TiO2 composite nanomaterial is 12%, the pretreated base fabric in S1 is immersed in the carbon nanotube / TiO2 composite nanomaterial solution, the immersion time is 3h, the pretreated base fabric is subjected to electric field treatment during the immersion process, the electric field treatment field strength is 1.56kV / m, the electric field is a uniform electric field, the electric field direction is parallel to the warp direction of the base fabric, and the once treated fabric is obtained after being taken out and dried;
[0059] S3: subjecting the once treated fabric in S2 to a heat setting and stretching treatment for 15 minutes, wherein the heat setting treatment temperature is 120° C. and the stretching amplitude during the heat setting treatment is 1.5, thereby obtaining a nano self-cleaning fabric;
[0060] S4: Sewing the nano self-cleaning fabric in S3 to the outer layer of the jacket to obtain a jacket made of the nano self-cleaning fabric.
[0061] Embodiment 2
[0062] This embodiment provides a jacket made of nano self-cleaning fabric, and the preparation process is as follows:
[0063] S1: The polyester / silver composite fabric is immersed in a 10% sodium hydroxide solution for 2 hours. The warp yarn of the polyester / silver composite fabric is a polyester / silver composite yarn, and the weft yarn is a polyester yarn. The warp yarn production process is to use polyester fiber as the core yarn and silver nanowire as the wrapping yarn for wrapping spinning. The number of polyester fibers and silver nanowires in each warp yarn is 3F and 5F respectively, and the diameter of the silver nanowire is 200nm. The fineness and number of polyester fibers in the warp yarn and weft yarn are consistent, and the fineness is 4D respectively. The warp yarn density is 30 strands / cm, and the weft yarn density is 45 strands / cm. After taking out and drying, a 0.5% methyl methacrylate silane solution is sprayed on the polyester / silver composite fabric for 30 minutes to obtain a pretreated base fabric.
[0064] S2: Add polyacrylonitrile and TiO2 powder into dimethyl sulfoxide to obtain polyacrylonitrile TiO2 solution, put carbon nanotubes into the polyacrylonitrile TiO2 solution, and obtain carbon nanotube / TiO2 precursor sol by ultrasonic dispersion. The mass ratio of polyacrylonitrile, TiO2, dimethyl sulfoxide and carbon nanotubes in the carbon nanotube / TiO2 precursor sol is 10:35:45:20. The carbon nanotube / TiO2 precursor sol is dried, ground, and calcined to obtain preliminary carbon nanotube / TiO2 composite nanomaterial. The carbon nanotube / TiO2 composite nanomaterial in S23 is irradiated with ultraviolet light at a wavelength of 360nm to obtain carbon nanotube / TiO2 composite nanomaterial. Nanotube / TiO2 composite nanomaterial, the particle diameter of carbon nanotube / TiO2 composite nanomaterial is 200nm; adding carbon nanotube / TiO2 composite nanomaterial into water to obtain carbon nanotube / TiO2 composite nanomaterial solution, the solution concentration of carbon nanotube / TiO2 composite nanomaterial is 12%, the pretreated base fabric in S1 is immersed in the carbon nanotube / TiO2 composite nanomaterial solution, the immersion time is 3h, the pretreated base fabric is subjected to electric field treatment during the immersion process, the electric field treatment field strength is 1.56kV / m, the electric field is a uniform electric field, the electric field direction is parallel to the warp direction of the base fabric, and the once treated fabric is obtained after being taken out and dried;
[0065] S3: subjecting the once treated fabric in S2 to a heat setting and stretching treatment for 15 minutes, wherein the heat setting treatment temperature is 120° C. and the stretching amplitude during the heat setting treatment is 1.5, thereby obtaining a nano self-cleaning fabric;
[0066] S4: Sewing the nano self-cleaning fabric in S3 to the outer layer of the jacket to obtain a jacket made of the nano self-cleaning fabric.
[0067] Embodiment 3
[0068] This embodiment provides a jacket made of nano self-cleaning fabric, and the preparation process is as follows:
[0069] S1: The polyester / silver composite fabric is immersed in a 10% sodium hydroxide solution for 2 hours. The warp yarn of the polyester / silver composite fabric is a polyester / silver composite yarn, and the weft yarn is a polyester yarn. The warp yarn production process is to use polyester fiber as the core yarn and silver nanowire as the wrapping yarn for wrapping spinning. The number of polyester fibers and silver nanowires in each warp yarn is 3F and 5F respectively, and the diameter of the silver nanowire is 250nm. The fineness and number of polyester fibers in the warp yarn and weft yarn are consistent, and the fineness is 4D respectively. The warp yarn density is 30 strands / cm, and the weft yarn density is 45 strands / cm. After taking out and drying, a 0.5% methyl methacrylate silane solution is sprayed on the polyester / silver composite fabric for 30 minutes to obtain a pretreated base fabric.
[0070] S2: Add polyacrylonitrile and TiO2 powder into dimethyl sulfoxide to obtain polyacrylonitrile TiO2 solution, put carbon nanotubes into the polyacrylonitrile TiO2 solution, and obtain carbon nanotube / TiO2 precursor sol by ultrasonic dispersion. The mass ratio of polyacrylonitrile, TiO2, dimethyl sulfoxide and carbon nanotubes in the carbon nanotube / TiO2 precursor sol is 10:35:45:20. The carbon nanotube / TiO2 precursor sol is dried, ground, and calcined to obtain preliminary carbon nanotube / TiO2 composite nanomaterial. The carbon nanotube / TiO2 composite nanomaterial in S23 is irradiated with ultraviolet light at a wavelength of 360nm to obtain carbon nanotube / TiO2 composite nanomaterial. Nanotube / TiO2 composite nanomaterial, the particle diameter of carbon nanotube / TiO2 composite nanomaterial is 200nm; adding carbon nanotube / TiO2 composite nanomaterial into water to obtain carbon nanotube / TiO2 composite nanomaterial solution, the solution concentration of carbon nanotube / TiO2 composite nanomaterial is 12%, the pretreated base fabric in S1 is immersed in the carbon nanotube / TiO2 composite nanomaterial solution, the immersion time is 3h, the pretreated base fabric is subjected to electric field treatment during the immersion process, the electric field treatment field strength is 1.56kV / m, the electric field is a uniform electric field, the electric field direction is parallel to the warp direction of the base fabric, and the once treated fabric is obtained after being taken out and dried;
[0071] S3: subjecting the once treated fabric in S2 to a heat setting and stretching treatment for 15 minutes, wherein the heat setting treatment temperature is 120° C. and the stretching amplitude during the heat setting treatment is 1.5, thereby obtaining a nano self-cleaning fabric;
[0072] S4: Sewing the nano self-cleaning fabric in S3 to the outer layer of the jacket to obtain a jacket made of the nano self-cleaning fabric.
[0073] Embodiment 4
[0074] This embodiment provides a jacket made of nano self-cleaning fabric, and the preparation process is as follows:
[0075] S1: The polyester / silver composite fabric is immersed in a 10% sodium hydroxide solution for 2 hours. The warp yarn of the polyester / silver composite fabric is a polyester / silver composite yarn, and the weft yarn is a polyester yarn. The warp yarn production process is to use polyester fiber as the core yarn and silver nanowire as the wrapping yarn for wrapping spinning. The number of polyester fibers and silver nanowires in each warp yarn is 3F and 5F respectively, and the diameter of the silver nanowire is 300nm. The fineness and number of polyester fibers in the warp yarn and weft yarn are consistent, and the fineness is 4D respectively. The warp yarn density is 30 strands / cm, and the weft yarn density is 45 strands / cm. After taking out and drying, a 0.5% methyl methacrylate silane solution is sprayed on the polyester / silver composite fabric for 30 minutes to obtain a pretreated base fabric.
[0076] S2: Add polyacrylonitrile and TiO2 powder into dimethyl sulfoxide to obtain polyacrylonitrile TiO2 solution, put carbon nanotubes into the polyacrylonitrile TiO2 solution, and obtain carbon nanotube / TiO2 precursor sol by ultrasonic dispersion. The mass ratio of polyacrylonitrile, TiO2, dimethyl sulfoxide and carbon nanotubes in the carbon nanotube / TiO2 precursor sol is 10:35:45:20. The carbon nanotube / TiO2 precursor sol is dried, ground, and calcined to obtain preliminary carbon nanotube / TiO2 composite nanomaterial. The carbon nanotube / TiO2 composite nanomaterial in S23 is irradiated with ultraviolet light at a wavelength of 360nm to obtain carbon nanotube / TiO2 composite nanomaterial. Nanotube / TiO2 composite nanomaterial, the particle diameter of carbon nanotube / TiO2 composite nanomaterial is 200nm; adding carbon nanotube / TiO2 composite nanomaterial into water to obtain carbon nanotube / TiO2 composite nanomaterial solution, the solution concentration of carbon nanotube / TiO2 composite nanomaterial is 12%, the pretreated base fabric in S1 is immersed in the carbon nanotube / TiO2 composite nanomaterial solution, the immersion time is 3h, the pretreated base fabric is subjected to electric field treatment during the immersion process, the electric field treatment field strength is 1.56kV / m, the electric field is a uniform electric field, the electric field direction is parallel to the warp direction of the base fabric, and the once treated fabric is obtained after being taken out and dried;
[0077] S3: subjecting the once treated fabric in S2 to a heat setting and stretching treatment for 15 minutes, wherein the heat setting treatment temperature is 120° C. and the stretching amplitude during the heat setting treatment is 1.5, thereby obtaining a nano self-cleaning fabric;
[0078] S4: Sewing the nano self-cleaning fabric in S3 to the outer layer of the jacket to obtain a jacket made of the nano self-cleaning fabric.
[0079] Embodiment 5
[0080] This embodiment provides a jacket made of nano self-cleaning fabric, and the preparation process is as follows:
[0081] S1: The polyester / silver composite fabric is immersed in a 10% sodium hydroxide solution for 2 hours. The warp yarn of the polyester / silver composite fabric is a polyester / silver composite yarn, and the weft yarn is a polyester yarn. The warp yarn production process is to use polyester fiber as the core yarn and silver nanowire as the wrapping yarn for wrapping spinning. The number of polyester fibers and silver nanowires in each warp yarn is 3F and 5F respectively, and the diameter of the silver nanowire is 350nm. The fineness and number of polyester fibers in the warp yarn and weft yarn are consistent, and the fineness is 4D respectively. The warp yarn density is 30 strands / cm, and the weft yarn density is 45 strands / cm. After taking out and drying, a 0.5% methyl methacrylate silane solution is sprayed on the polyester / silver composite fabric for 30 minutes to obtain a pretreated base fabric.
[0082] S2: Add polyacrylonitrile and TiO2 powder into dimethyl sulfoxide to obtain polyacrylonitrile TiO2 solution, put carbon nanotubes into the polyacrylonitrile TiO2 solution, and obtain carbon nanotube / TiO2 precursor sol by ultrasonic dispersion. The mass ratio of polyacrylonitrile, TiO2, dimethyl sulfoxide and carbon nanotubes in the carbon nanotube / TiO2 precursor sol is 10:35:45:20. The carbon nanotube / TiO2 precursor sol is dried, ground, and calcined to obtain preliminary carbon nanotube / TiO2 composite nanomaterial. The carbon nanotube / TiO2 composite nanomaterial in S23 is irradiated with ultraviolet light at a wavelength of 360nm to obtain carbon nanotube / TiO2 composite nanomaterial. Nanotube / TiO2 composite nanomaterial, the particle diameter of carbon nanotube / TiO2 composite nanomaterial is 200nm; adding carbon nanotube / TiO2 composite nanomaterial into water to obtain carbon nanotube / TiO2 composite nanomaterial solution, the solution concentration of carbon nanotube / TiO2 composite nanomaterial is 12%, the pretreated base fabric in S1 is immersed in the carbon nanotube / TiO2 composite nanomaterial solution, the immersion time is 3h, the pretreated base fabric is subjected to electric field treatment during the immersion process, the electric field treatment field strength is 1.56kV / m, the electric field is a uniform electric field, the electric field direction is parallel to the warp direction of the base fabric, and the once treated fabric is obtained after being taken out and dried;
[0083] S3: subjecting the once treated fabric in S2 to a heat setting and stretching treatment for 15 minutes, wherein the heat setting treatment temperature is 120° C. and the stretching amplitude during the heat setting treatment is 1.5, thereby obtaining a nano self-cleaning fabric;
[0084] S4: Sewing the nano self-cleaning fabric in S3 to the outer layer of the jacket to obtain a jacket made of the nano self-cleaning fabric.
[0085] Embodiment 6
[0086] This embodiment provides a jacket made of nano self-cleaning fabric, and the preparation process is as follows:
[0087] S1: The polyester / silver composite fabric is immersed in a 10% sodium hydroxide solution for 2 hours. The warp yarn of the polyester / silver composite fabric is a polyester / silver composite yarn, and the weft yarn is a polyester yarn. The warp yarn production process is to use polyester fiber as the core yarn and silver nanowire as the wrapping yarn for wrapping spinning. The number of polyester fibers and silver nanowires in each warp yarn is 3F and 5F respectively, and the diameter of the silver nanowire is 250nm. The fineness and number of polyester fibers in the warp yarn and weft yarn are consistent, and the fineness is 4D respectively. The warp yarn density is 30 strands / cm, and the weft yarn density is 45 strands / cm. After taking out and drying, a 0.5% methyl methacrylate silane solution is sprayed on the polyester / silver composite fabric for 30 minutes to obtain a pretreated base fabric.
[0088] S2: Add polyacrylonitrile and TiO2 powder into dimethyl sulfoxide to obtain polyacrylonitrile TiO2 solution, put carbon nanotubes into the polyacrylonitrile TiO2 solution, and obtain carbon nanotube / TiO2 precursor sol by ultrasonic dispersion. The mass ratio of polyacrylonitrile, TiO2, dimethyl sulfoxide and carbon nanotubes in the carbon nanotube / TiO2 precursor sol is 5:35:45:20. The carbon nanotube / TiO2 precursor sol is dried, ground, and calcined to obtain preliminary carbon nanotube / TiO2 composite nanomaterial. The carbon nanotube / TiO2 composite nanomaterial in S23 is irradiated with ultraviolet light at a wavelength of 360nm to obtain carbon nanotubes. The carbon nanotube / TiO2 composite nanomaterial has a particle diameter of 200nm; the carbon nanotube / TiO2 composite nanomaterial is added into water to obtain a carbon nanotube / TiO2 composite nanomaterial solution, the solution concentration of the carbon nanotube / TiO2 composite nanomaterial is 12%, the pretreated base fabric in S1 is immersed in the carbon nanotube / TiO2 composite nanomaterial solution, the immersion time is 3h, the pretreated base fabric is subjected to electric field treatment during the immersion process, the electric field treatment field strength is 1.56kV / m, the electric field is a uniform electric field, the electric field direction is parallel to the warp direction of the base fabric, and the once treated fabric is obtained after being taken out and dried;
[0089] S3: subjecting the once treated fabric in S2 to a heat setting and stretching treatment for 15 minutes, wherein the heat setting treatment temperature is 120° C. and the stretching amplitude during the heat setting treatment is 1.5, thereby obtaining a nano self-cleaning fabric;
[0090] S4: Sewing the nano self-cleaning fabric in S3 to the outer layer of the jacket to obtain a jacket made of the nano self-cleaning fabric.
[0091] Embodiment 7
[0092] This embodiment provides a jacket made of nano self-cleaning fabric, and the preparation process is as follows:
[0093] S1: The polyester / silver composite fabric is immersed in a 10% sodium hydroxide solution for 2 hours. The warp yarn of the polyester / silver composite fabric is a polyester / silver composite yarn, and the weft yarn is a polyester yarn. The warp yarn production process is to use polyester fiber as the core yarn and silver nanowire as the wrapping yarn for wrapping spinning. The number of polyester fibers and silver nanowires in each warp yarn is 3F and 5F respectively, and the diameter of the silver nanowire is 250nm. The fineness and number of polyester fibers in the warp yarn and weft yarn are consistent, and the fineness is 4D respectively. The warp yarn density is 30 strands / cm, and the weft yarn density is 45 strands / cm. After taking out and drying, a 0.5% methyl methacrylate silane solution is sprayed on the polyester / silver composite fabric for 30 minutes to obtain a pretreated base fabric.
[0094] S2: Add polyacrylonitrile and TiO2 powder into dimethyl sulfoxide to obtain polyacrylonitrile TiO2 solution, put carbon nanotubes into the polyacrylonitrile TiO2 solution, and obtain carbon nanotube / TiO2 precursor sol by ultrasonic dispersion. The mass ratio of polyacrylonitrile, TiO2, dimethyl sulfoxide and carbon nanotubes in the carbon nanotube / TiO2 precursor sol is 15:35:45:20. The carbon nanotube / TiO2 precursor sol is dried, ground, and calcined to obtain preliminary carbon nanotube / TiO2 composite nanomaterial. The carbon nanotube / TiO2 composite nanomaterial in S23 is irradiated with ultraviolet light at a wavelength of 360nm to obtain carbon nanotube / TiO2 composite nanomaterial. Nanotube / TiO2 composite nanomaterial, the particle diameter of carbon nanotube / TiO2 composite nanomaterial is 200nm; adding carbon nanotube / TiO2 composite nanomaterial into water to obtain carbon nanotube / TiO2 composite nanomaterial solution, the solution concentration of carbon nanotube / TiO2 composite nanomaterial is 12%, the pretreated base fabric in S1 is immersed in the carbon nanotube / TiO2 composite nanomaterial solution, the immersion time is 3h, the pretreated base fabric is subjected to electric field treatment during the immersion process, the electric field treatment field strength is 1.56kV / m, the electric field is a uniform electric field, the electric field direction is parallel to the warp direction of the base fabric, and the once treated fabric is obtained after being taken out and dried;
[0095] S3: subjecting the once treated fabric in S2 to a heat setting and stretching treatment for 15 minutes, wherein the heat setting treatment temperature is 120° C. and the stretching amplitude during the heat setting treatment is 1.5, thereby obtaining a nano self-cleaning fabric;
[0096] S4: Sewing the nano self-cleaning fabric in S3 to the outer layer of the jacket to obtain a jacket made of the nano self-cleaning fabric.
[0097] Embodiment 8
[0098] This embodiment provides a jacket made of nano self-cleaning fabric, and the preparation process is as follows:
[0099] S1: The polyester / silver composite fabric is immersed in a 10% sodium hydroxide solution for 2 hours. The warp yarn of the polyester / silver composite fabric is a polyester / silver composite yarn, and the weft yarn is a polyester yarn. The warp yarn production process is to use polyester fiber as the core yarn and silver nanowire as the wrapping yarn for wrapping spinning. The number of polyester fibers and silver nanowires in each warp yarn is 3F and 5F respectively, and the diameter of the silver nanowire is 250nm. The fineness and number of polyester fibers in the warp yarn and weft yarn are consistent, and the fineness is 4D respectively. The warp yarn density is 30 strands / cm, and the weft yarn density is 45 strands / cm. After taking out and drying, a 0.5% methyl methacrylate silane solution is sprayed on the polyester / silver composite fabric for 30 minutes to obtain a pretreated base fabric.
[0100] S2: Add polyacrylonitrile and TiO2 powder into dimethyl sulfoxide to obtain polyacrylonitrile TiO2 solution, put carbon nanotubes into the polyacrylonitrile TiO2 solution, and obtain carbon nanotube / TiO2 precursor sol by ultrasonic dispersion. The mass ratio of polyacrylonitrile, TiO2, dimethyl sulfoxide and carbon nanotubes in the carbon nanotube / TiO2 precursor sol is 20:35:45:20. The carbon nanotube / TiO2 precursor sol is dried, ground, and calcined to obtain preliminary carbon nanotube / TiO2 composite nanomaterial. The carbon nanotube / TiO2 composite nanomaterial in S23 is irradiated with ultraviolet light at a wavelength of 360nm to obtain carbon nanotube / TiO2 composite nanomaterial. Nanotube / TiO2 composite nanomaterial, the particle diameter of carbon nanotube / TiO2 composite nanomaterial is 200nm; adding carbon nanotube / TiO2 composite nanomaterial into water to obtain carbon nanotube / TiO2 composite nanomaterial solution, the solution concentration of carbon nanotube / TiO2 composite nanomaterial is 12%, the pretreated base fabric in S1 is immersed in the carbon nanotube / TiO2 composite nanomaterial solution, the immersion time is 3h, the pretreated base fabric is subjected to electric field treatment during the immersion process, the electric field treatment field strength is 1.56kV / m, the electric field is a uniform electric field, the electric field direction is parallel to the warp direction of the base fabric, and the once treated fabric is obtained after being taken out and dried;
[0101] S3: subjecting the once treated fabric in S2 to a heat setting and stretching treatment for 15 minutes, wherein the heat setting treatment temperature is 120° C. and the stretching amplitude during the heat setting treatment is 1.5, thereby obtaining a nano self-cleaning fabric;
[0102] S4: Sewing the nano self-cleaning fabric in S3 to the outer layer of the jacket to obtain a jacket made of the nano self-cleaning fabric.
[0103] Embodiment 9
[0104] This embodiment provides a jacket made of nano self-cleaning fabric, and the preparation process is as follows:
[0105] S1: The polyester / silver composite fabric is immersed in a 10% sodium hydroxide solution for 2 hours. The warp yarn of the polyester / silver composite fabric is a polyester / silver composite yarn, and the weft yarn is a polyester yarn. The warp yarn production process is to use polyester fiber as the core yarn and silver nanowire as the wrapping yarn for wrapping spinning. The number of polyester fibers and silver nanowires in each warp yarn is 3F and 5F respectively, and the diameter of the silver nanowire is 250nm. The fineness and number of polyester fibers in the warp yarn and weft yarn are consistent, and the fineness is 4D respectively. The warp yarn density is 30 strands / cm, and the weft yarn density is 45 strands / cm. After taking out and drying, a 0.5% methyl methacrylate silane solution is sprayed on the polyester / silver composite fabric for 30 minutes to obtain a pretreated base fabric.
[0106] S2: Add polyacrylonitrile and TiO2 powder into dimethyl sulfoxide to obtain polyacrylonitrile TiO2 solution, put carbon nanotubes into the polyacrylonitrile TiO2 solution, and obtain carbon nanotube / TiO2 precursor sol by ultrasonic dispersion. The mass ratio of polyacrylonitrile, TiO2, dimethyl sulfoxide and carbon nanotubes in the carbon nanotube / TiO2 precursor sol is 25:35:45:20. The carbon nanotube / TiO2 precursor sol is dried, ground, and calcined to obtain preliminary carbon nanotube / TiO2 composite nanomaterial. The carbon nanotube / TiO2 composite nanomaterial in S23 is irradiated with ultraviolet light at a wavelength of 360nm to obtain carbon nanotube / TiO2 composite nanomaterial. Nanotube / TiO2 composite nanomaterial, the particle diameter of carbon nanotube / TiO2 composite nanomaterial is 200nm; adding carbon nanotube / TiO2 composite nanomaterial into water to obtain carbon nanotube / TiO2 composite nanomaterial solution, the solution concentration of carbon nanotube / TiO2 composite nanomaterial is 12%, the pretreated base fabric in S1 is immersed in the carbon nanotube / TiO2 composite nanomaterial solution, the immersion time is 3h, the pretreated base fabric is subjected to electric field treatment during the immersion process, the electric field treatment field strength is 1.56kV / m, the electric field is a uniform electric field, the electric field direction is parallel to the warp direction of the base fabric, and the once treated fabric is obtained after being taken out and dried;
[0107] S3: subjecting the once treated fabric in S2 to a heat setting and stretching treatment for 15 minutes, wherein the heat setting treatment temperature is 120° C. and the stretching amplitude during the heat setting treatment is 1.5, thereby obtaining a nano self-cleaning fabric;
[0108] S4: Sewing the nano self-cleaning fabric in S3 to the outer layer of the jacket to obtain a jacket made of the nano self-cleaning fabric.
[0109] Comparative Example 1
[0110] S1: The polyester fabric is immersed in a 10% sodium hydroxide solution for 2 hours. The warp and weft yarns of the polyester fabric are both polyester yarns. The fineness and number of polyester fibers in the warp and weft yarns are consistent, which are 4D and 3F respectively. The warp yarn density is 30 yarns / cm, and the weft yarn density is 45 yarns / cm. After taking out and drying, a 0.5% methyl methacrylate silane solution is sprayed on the polyester fabric for 30 minutes to obtain a pretreated base fabric.
[0111] S2: Immerse the pretreated base fabric in S1 in the TiO2 nano solution for 3 hours, take it out and dry it to obtain a treated fabric;
[0112] S3: Immerse the primary treated fabric in S2 in a 15% silver nitrate solution for 45 minutes to obtain a secondary treated fabric;
[0113] S4: The secondary treated fabric in S3 is combined with the outer layer of the jacket to obtain a jacket made of nano self-cleaning fabric.
[0114] Samples from Examples 1 to 9 and Comparative Example 1 were taken, 15 mg / L methyl orange solution was placed on the samples, and self-cleaning ability tests were performed under normal lighting conditions and low lighting conditions, respectively. The lighting conditions under normal lighting conditions and low lighting conditions were 2000 Lux and 100 Lux, respectively. The methyl orange concentration was detected using a spectrophotometer, and the degradation time was recorded when the methyl orange solution concentration dropped to 20% of the initial concentration. The test results are shown in Table 1:
[0115] Table 1 Self-cleaning test data of Examples 1 to 9 and Comparative Example 1 under normal conditions and low light conditions
[0116]
[0117]
[0118] It can be seen from Table 1 that the normal light degradation time and the low light degradation time of Examples 1 to 9 are both shorter than the normal light degradation time and the low light degradation time in Comparative Example 1. Therefore, the preparation process of the jacket made of the nano self-cleaning fabric of the present invention is superior.
[0119] In Examples 1 to 5, as the diameter of the silver nanowire gradually increases, the degradation time under normal illumination and the degradation time under low illumination both decrease first and then increase. This is because as the diameter of the silver nanowire increases, its light absorption and scattering ability will also increase, and the carbon nanotubes and the nanosilver wires are connected by chemical bonds, which can reduce the contact resistance between the two and greatly improve the electrical conductivity of the material. It also affects the orientation of the carbon nanotubes, which can enhance the scattering and reflection ability of the carbon nanotubes, improve the ability of titanium dioxide particles to obtain light sources, enhance the self-cleaning conditions under normal illumination conditions, and enhance the self-cleaning effect under low illumination conditions; however, as the diameter increases, the specific surface area decreases, the number of active sites decreases, affecting the photocatalytic efficiency, and the separation efficiency of the photogenerated charges decreases, making it difficult for the self-cleaning effect to occur under low illumination conditions. The best embodiment is Example 3.
[0120] In Example 3 and Examples 6 to 9, as the mass proportion of polyacrylonitrile in the carbon nanotube / TiO2 precursor sol increases, the normal light degradation time and the low light degradation time both decrease first and then increase. This is because the increase of polyacrylonitrile can improve the dispersion of the photocatalyst on the substrate, thereby increasing the contact area between the photocatalyst and the pollutant and improving the photocatalytic efficiency. After polyacrylonitrile and carbon nanotubes are mixed, under the action of surface tension, the carbon nanotubes tend to be arranged along the axial orientation of the nanofibers, which improves the orientation of the carbon nanotubes. Carbon nanotubes with high orientation are more conducive to the rapid transmission of electrons, reduce the recombination probability of electrons during the transmission process, and further improve the photocatalytic efficiency under low light conditions; but too much polyacrylonitrile causes titanium dioxide to be excessively absorbed, reducing the contact opportunity between titanium dioxide and pollutants, thereby reducing the photocatalytic efficiency under low light conditions. The best embodiment is Example 7.
[0121] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A preparation process of a jacket made of nano self-cleaning fabric, characterized in that: The following steps are involved: S1: immersing the base fabric in an alkaline solution for 1-2 hours, taking it out and drying it, and then performing a surface active treatment to obtain a pretreated base fabric; S2: adding carbon nanotube / TiO2 composite nanomaterial into water to obtain carbon nanotube / TiO2 composite nanomaterial solution, immersing the pretreated base fabric in S1 into the carbon nanotube / TiO2 composite nanomaterial solution for 2-4 hours, taking out and drying to obtain a treated fabric; S3: subjecting the once treated fabric in S2 to a heat setting and stretching treatment for 10-20 minutes to obtain a nano self-cleaning fabric; S4: Sewing the nano self-cleaning fabric described in S3 to the outer layer of the jacket to obtain a jacket made of the nano self-cleaning fabric.
2. The preparation process of a jacket made of nano self-cleaning fabric according to claim 1, characterized in that: The base fabric is polyester / silver composite fabric with a warp density of 25-30 yarns / cm and a weft density of 45-50 yarns / cm.
3. The preparation process of a jacket made of nano self-cleaning fabric according to claim 2, characterized in that: The warp yarn of the base fabric is polyester / silver composite yarn, and the weft yarn is polyester yarn. The warp yarn production process is to use polyester fiber as core yarn and silver nanowire as wrapping yarn for wrapping spinning. The number of polyester fibers and silver nanowires in each warp yarn is 2-3F and 4-5F respectively, and the diameter of the silver nanowire is 200-300nm. The fineness and number of polyester fibers in the warp and weft yarns are consistent, and the fineness is 3-5D respectively.
4. The preparation process of a jacket made of nano self-cleaning fabric according to claim 1, characterized in that: The alkaline solution in S1 is a sodium hydroxide solution with a concentration of 10-15%, and the surface active treatment is to spray a 0.5-1% methyl methacrylate silane solution on the base fabric after being immersed in the alkaline solution, and the spraying time is 30-45 minutes.
5. The preparation process of a jacket made of nano self-cleaning fabric according to claim 1, characterized in that: The preparation method of the carbon nanotube / TiO2 composite nanomaterial in S2 is as follows: S21: adding polyacrylonitrile and TiO2 powder into dimethyl sulfoxide to obtain a polyacrylonitrile TiO2 solution; S22: placing carbon nanotubes into the polyacrylonitrile TiO2 solution in S21, and obtaining a carbon nanotube / TiO2 precursor sol by ultrasonic dispersion; S23: drying and grinding the carbon nanotube / TiO2 precursor sol in S22, and then calcining to obtain a preliminary carbon nanotube / TiO2 composite nanomaterial; S24: irradiating the carbon nanotube / TiO2 composite nanomaterial in S23 with ultraviolet light at a wavelength of 340-380 nm to obtain a carbon nanotube / TiO2 composite nanomaterial.
6. The preparation process of a jacket made of nano self-cleaning fabric according to claim 5, characterized in that: The mass ratio of polyacrylonitrile, TiO2, dimethyl sulfoxide and carbon nanotubes in the carbon nanotube / TiO2 precursor sol in S22 is 10-20:30-40:40-50:20-30.
7. The preparation process of a jacket made of nano self-cleaning fabric according to claim 1, characterized in that: The particle diameter of the carbon nanotube / TiO2 composite nanomaterial in the S2 is 100-300nm, and the solution concentration of the carbon nanotube / TiO2 composite nanomaterial is 10-12%.
8. The preparation process of a jacket made of nano self-cleaning fabric according to claim 1, characterized in that: The pretreated base fabric in S2 is subjected to electric field treatment during the dipping process, the electric field treatment field strength is 0.33-2.94 kV / m, the electric field is a uniform electric field, and the direction of the electric field is parallel to the warp direction of the base fabric.
9. The preparation process of a jacket made of nano self-cleaning fabric according to claim 1, characterized in that: The temperature of the heat setting treatment in S3 is 110-130° C., the stretching amplitude during the heat setting treatment is 1.5-2, and the stretching direction is parallel to the warp direction of the base fabric.
10. A jacket made of nano self-cleaning fabric, characterized in that: A preparation process for a jacket made of a nano self-cleaning fabric according to any one of claims 1-9.